THE EFFECTIVENESS OF AROMATHERAPY IN REDUCING NAUSEA AND VOMITING ON PREGNANT WOMEN IN TRIMESTER I: LITERATURE REVIEW - Lilis Mamuroh; Sukmawati Sukmawati; Furkon Nurhakim (Journal of Maternity Care and Reproductive Health, 2021)
Pregnancy is a normal process that begins with intrauterine growth and development of the fetus, starting from conception to delivery. During pregnancy, there are physiological changes that will be felt by women, one of which is nausea and vomiting.. Excessive and untreated nausea and vomiting can lead to worse pregnancy problems.. The purpose of the literature study was to determine the effectiveness of aromatherapy in reducing nausea and vomiting in first trimester pregnant women. This research method is literature study, by searching using Efidence Based Practice (EBP) from databases such as Pubmed, Proquest, and Google Scholar. There are 7 articles based on the results of searching using the PICO technique. The instrument is a critical appraisal check from JBI QARI. After conducting an article search, 7 research articles were selected that match the inclusion criteria. The results of the analysis found that there was a decrease in nausea and vomiting in pregnant women who were given aromatherapy interventions, be it lemon, ginger, peppermint, lavender, and citrus aromatherapy but havent fuond the most effective one yet. econcluded that the administration of aromatherapy is effective/influential in dealing with nausea and vomiting in pregnant women.